2021
DOI: 10.1186/s13567-021-00965-3
|View full text |Cite
|
Sign up to set email alerts
|

Damage to intestinal barrier integrity in piglets caused by porcine reproductive and respiratory syndrome virus infection

Abstract: Porcine reproductive and respiratory syndrome (PRRS) induces respiratory disease and reproductive failure accompanied by gastroenteritis-like symptoms. The mechanism of intestinal barrier injury caused by PRRSV infection in piglets has yet to be investigated. An in vivo PRRSV-induced model was established in 30-day-old piglets by the intramuscular injection of 2 mL of 104 TCID50/mL PRRSV for 15 days. Observations of PRRSV replication and histology were conducted in the lungs and intestine, and goblet cell coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 56 publications
2
10
0
Order By: Relevance
“…Occludin and Claudin-1 are crucial to TJs [ 62 , 63 ]. The changes in gene expression of ZO-1 , Occludin, and Claudin-1 in this study suggest the destruction of ileal TJs after XMX infection, which can be observed in other reports about viral infection [ 64 , 65 , 66 , 67 , 68 , 69 ]. The destruction of ileum villi after infection indicates that the intestinal absorption of nutrients is reduced, which may cause Muscovy duck dwarfism.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Occludin and Claudin-1 are crucial to TJs [ 62 , 63 ]. The changes in gene expression of ZO-1 , Occludin, and Claudin-1 in this study suggest the destruction of ileal TJs after XMX infection, which can be observed in other reports about viral infection [ 64 , 65 , 66 , 67 , 68 , 69 ]. The destruction of ileum villi after infection indicates that the intestinal absorption of nutrients is reduced, which may cause Muscovy duck dwarfism.…”
Section: Discussionsupporting
confidence: 86%
“…Occludin and Claudin-1 are crucial to TJs [62,63]. The changes in gene expression of ZO-1, Occludin, and Claudin-1 in this study suggest the destruction of ileal TJs after XMX infection, which can be observed in other reports about viral infection [64][65][66][67][68][69]. The destruction of ileum villi after infection All WPF sequences were divided into three groups to verify the above-mentioned result, namely, GPV, MDPV and rMDPV, based on the three branches of the complete genome phylogenetic tree (Figure 1A).…”
Section: Discussionsupporting
confidence: 81%
“…(2) PRRSV evades host cell-mediated immunity and causes the delayed onset of the Th1 immune response [ 28 , 29 ]. (3) PRRSV damages immune barriers [ 30 ]. In addition, PRRSV replicates in PAMs causes dysfunction or even cell death by necrosis and apoptosis [ 31 ], impairing their antigen-presenting function.…”
Section: Discussionmentioning
confidence: 99%
“…Since IPIM were also shown to be susceptible to infection by a PRRSV field strain and exhibited a high infection titer (10 7 TCID 50 /mL), this cell line is expected to be useful for isolating PRRSV from field samples and developing new LAV strains. Furthermore, it is reported that PRRSV infection impairs intestinal integrity by damaging physical and immune barriers in the intestine by inducing inflammation, which may be related to the regulation of the gut-lung axis ( 44 ). Thus, it is conceivable that IPIM or PIM are valuable tools for investigating the mechanisms by which PRRSV affects intestinal mucosal inflammation and the pathogenesis of PRRSV-induced diarrhea.…”
Section: Discussionmentioning
confidence: 99%